Evidence of ultra-low-k dielectric material degradation and nanostructure alteration of the Cu/ultra-low-k interconnects in time-dependent dielectric breakdown failure - Lam, Jeffrey C. K. (2013)
Ultra-low-k time-dependent dielectric breakdown (TDDB) is one of the most important reliability issues in Cu/low-k technology development due to its weaker intrinsic breakdown strength compared to SiO2 dielectrics. With continuous technology scaling, this problem is further exacerbated for Cu/ultra-low-k interconnects. In this letter, the TDDB degradation behavior of ultra-low-k dielectric in Cu/ultra-low-k interconnects will be investigated by a method consisting of a combination of Raman with Fourier transform infrared vibrational microscopes. In TDDB tests on Cu/low-k interconnect, it was found that intrinsic degradation of the ultra-low-k dielectric would first occur under electrical field stress. Upon further electrical field stress, the ultra-low-k dielectric degradation would be accelerated due to Ta ions migration from the Ta/TaN barrier bi-layer into the ultra-low-k dielectrics. In addition, no out-diffusion of Cu ions was observed in our investigation on Cu/Ta/TaN/ SiCOH structures.